Pengaruh Faktor Personal, Karakteristik Pekerjaan, Karakteristik Struktur dan Pengalaman Kerja terhadap Komitmen Organisasional - Joko, Fauzi Tri; Bodroastuti, Tri (Jurnal Ilmiah Aset, 2013)
The purpose of this study was to identify and analyze the influence of personal factor, work characteristics, structural characteristics and work experience on Organizational Commitment of UPTD employees on Regional Market Jatingaleh Semarang. The population in this study was all employees ofUPTD Market Jatingaleh Semarang totaling 48 employees. The entire population was sampled so that the number of samples used by 48 employees. The analytical tool used in this study was multiple linear regression, with the first data was examined by validity and reliability testing. The results showed that there was positive influence of factor of personal, work characteristics, structural characteristics and work experience on organizational commitment either partially or simultaneously. It means if factor of personal, work characteristics, structural characteristics and work experience increase, the organizational commitment will increase.